Newman and Quasi-Fideism: A Reply to Duncan Pritchard - Aquino, Frederick D. (Heythrop journal, 2023)
In recent years, Duncan Pritchard has developed a position in religious epistemology called quasi-fideism that he claims traces back to John Henry Newman's treatment of the rationality of religious belief. In this paper, we give three reasons to think that Pritchard's reading of Newman as a quasi-fideist is mistaken. First, Newman's parity argument does not claim that religious and non-religious beliefs are on a par because both are groundless; instead, for Newman, they are on a par because both often stem from implicit rather than explicit reasoning. Second, pace Pritchard, Newman's distinction between simple and complex assent does not map onto the Wittgensteinian distinction between groundless hinge commitments and beliefs that flow from these hinges. For Newman, simple and complex assent differ in terms of the believer's level of awareness of their grounds. Third, and finally, Newman does not reject Locke's evidentialism in toto. Instead, he argues that certitude is not restricted to beliefs stemming from intuition and demonstration but often rightly includes probabilistically supported (or fallibly evidenced) beliefs.